Frequency of Postoperative Maxillomandibular Fixation Following Open Reduction and Internal Fixation in Maxillofacial Fractures: Postoperative Maxillomandibular Fixation in Facial Fractures - Shahbaz, Mahrukh; Aqib Sohail; Fareed ud Din Ahmad Chishti; Ali Ammar Hasan; Muhammad Abubakr Bin Nauman; Muneeba Shoaib (Journal of University College of Medicine and Dentistry, 2025)
Objective: To determine the frequency of postoperative maxillomandibular fixation (MMF) required after open reduction and internal fixation (ORIF) for restoring premorbid occlusion in patients with maxillary and mandibular fractures. Methodology: This cross-sectional analytical study was conducted in Department of Oral & Maxillofacial Surgery, Ghurki Trust Teaching Hospital, Lahore. Patients aged 12 to 60 years of either gender presenting with maxillary or mandibular fractures were included in the study. ORIF procedure was performed under General Anesthesia with nasal intubation in all cases of maxillary and mandibular fractures under inclusive criteria. Then patients were followed-up in OPD for 2 weeks and evaluated for postoperative malocclusion, and MMF was done for 4 weeks under local anesthesia to restore premorbid occlusion Results: A total of 382 patients that met the study criteria were included in this study. Out of these, 240 (62.8%) were men and 142 were women. Mean age of the patients was 30.34±9.40 years. The maxilla was the site of fracture in 180 cases (47.1%), while among mandibular fractures, the parasymphyseal region was involved in 172 cases (45.3%) and the angle in 29 cases (7.6%). The overall frequency of postoperative MMF was 53.9%. Among the complications observed, wound dehiscence occurred in 4.5% of cases with MMF and 2.6% without it; infection rates were 6.3% with MMF and 3.9% without. Malocclusion was reported in 0% of cases with MMF compared to 0.8% without MMF. Conclusion: The findings of this study support the use of post-operative MMF after ORIF of patients with malocclusion in maxillary and mandibular fractures. This treatment modality may offer a safe, effective, and reliable means of achieving optimal occlusal outcomes and improving patient satisfaction; however, further controlled studies are needed to establish its role in standard care.